Comparison of the viscosity of trehalose and sucrose solutions at various temperatures: Effect of guar gum addition - Galmarini, Mara Virginia (2011)
Fil: Galmarini, Mara Virginia. Pontificia Universidad Católica Argentina. Facultad de Ciencias Agrarias; Argentina